Asosiasi Ikan Karang Pada Media Transplantasi Rangka Model Penyu di Pulau Barrang Caddi, Kota Makassar - Muh. Imran Lapong; Krisnayanti Krisnayanti; Fathuddin Fathuddin; Sri Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Recent studies show the importance of artificial structures in supporting the recovery of coral reef ecosystems, particularly in improving the association of reef fish that play an important role in the ecological balance of tropical seas. The innovation in the use of turtle-shaped transplant skeletons is the main highlight because it is able to attract higher biodiversity than conventional methods. This study aims to evaluate the parameters of water quality, diversity index, and abundance of reef fish species associated with the transplant structure. Data collection was carried out using the Underwater Visual Census (UVC) method at two different sampling moments of the season. The first sampling is during the rainy season, and the second sampling is during the dry season. The environmental parameters measured included salinity, temperature, pH, and water currents, while biotic indicators included the Shannon-Wiener diversity index (H') and species density (ind/m²). The results showed that all water quality parameters were within the standard range of marine quality for marine life (First side: salinity 32.6 ppt; temperature 31 °C; pH 7.7; current 0.05 m/s and second sampling: salinity 32 ppt; temperature 30.6 °C; pH 7.5; current 0.07 m/s). A total of sixteen species of fish were found to be associated with transplanting media, including Plotosus lineatus, Siganus margaritiferus, Ptereleotris heteroptera, Abudefduf vaigiensis, Chromis atripectoralis, Aeoliscus strigatus, Petroscirtes mitratus, Chaetodon octofactiatus, Abudefduf sexfactiatus, Meiacanthus grammistes, Cheilodipterus artus, Cheilinus chlorourus, Siganus virgatus, Chrysiptera parasema, Synanceia verrucosa and Sargocentron xantherythrum. The first sampling showed a lower diversity value (H' = 316.76; D = 2.3 ind/m²) compared to the second sampling (H' = 322.10; D = 3.28 ind/m²). This difference is influenced by dry season conditions that lead to increased clarity and penetration of sunlight, which significantly supports the abundance of biota. These findings confirm the potential of innovative transplant structure design in supporting sustainable coral fisheries conservation.